PEDIATRIC CRANIOFACIAL DISFIGUREMENT WITH AUTOLOGOUS RIBS BONE GRAFT RECONSTRUCTION - Anne Saputra; Wayan Niryana; Made Suka Adnyana (Neurologico Spinale Medico Chirurgico, 2018)
Pediatric reconstruction of the cranial defect is a challenging task, the standard reconstruction method has been bone grafting. The reconstruction of complex facial defects should satisfy both aesthetic and functional requirements. In the case of large defects, the use of craniofacial prostheses using autogenous bone is the material of choice because of its potential for revascularization and its osteoconductive properties. A 3-year-old patient has facial disfgurement as result from bone defciency following anterior skull base tumour resection. To minimize the associated functional and cosmetic problems, a number of reconstructive options are available to the surgeon including the use of autogenous and alloplastic implants. A computed tomography (CT) 3-dimensional reconstruction scan showed a large craniofacial defect as residual radical skull base tumour resection. A transcranial approach by a neurosurgeon and plastic surgery was performed to reconstruct the defect using autologous rib bone graft. Six months after the reconstruction surgery, a defect of the craniofacial was narrowing without cranial nerve defcits.Complex reconstructions of extensive defects in craniofacial area can be achieved using autologous bone grafts. They yield reasonable functional and aesthetic outcomes and noticeably improves the qualityof life.